Estado nutricional y su relación con actividad física y hábitos alimenticios en estudiantes de Medicina de la Universidad Nacional de Loja - Arévalo Ramón, Marcos Daniel (2015)
Excess weight, eating behavior disorders and lack of physical activity in young people is an area of national concern, hence the present work is to determine the nutritional status, physical activity and eating habits in students studying medicine at the National University of Loja in a sample of 281 students from different cycles and modules, the study is quantitative, transversal and correlational. The index of diet quality to meet dietary habits, physical activity by applying a survey and nutritional status for the body mass index was applied. The results show that 75.8% have normal weight and 18.5% overweight. The overweight 92.31% followed by 89.2% with 75% normal weight and underweight need to improve their eating habits. Finally, 48.08% overweight are not physically active. These data show that the population studied normal as those who are overweight and obesity even worse if not improve your eating habits for a balanced diet will be prone to developing noncommunicable diseases nutritional status. Keywords: Nutritional status, physical activity, eating habits.